2018
DOI: 10.1063/1.5019469
|View full text |Cite
|
Sign up to set email alerts
|

Electrogates for stop-and-go control of liquid flow in microfluidics

Abstract: Diagnostics based on microfluidic devices necessitate specific reagents, flow conditions, and kinetics for optimal performance. Such an optimization is often achieved using assay-specific microfluidic chip designs or systems with external liquid pumps. Here, we present “electrogates” for stop-and-go control of flow of liquids in capillary-driven microfluidic chips by combining liquid pinning and electrowetting. Electrogates are simple to fabricate and efficient: a sample pipetted to a microfluidic chip flows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Arango et al reported the control of microfluid transportation through building electrogates in the microchannel. [94] Different from the aforementioned integrated electrodes with hydrophobic SAMs, the electrodes they reported have semicircular trench patterns and were not modified by hydrophobic functional molecules. Integration of stimuli-responsive polymer brushes into microchannel surfaces provides advanced strategies for smart control of microscale flow.…”
Section: Liquid Surface Designmentioning
confidence: 91%
See 1 more Smart Citation
“…Arango et al reported the control of microfluid transportation through building electrogates in the microchannel. [94] Different from the aforementioned integrated electrodes with hydrophobic SAMs, the electrodes they reported have semicircular trench patterns and were not modified by hydrophobic functional molecules. Integration of stimuli-responsive polymer brushes into microchannel surfaces provides advanced strategies for smart control of microscale flow.…”
Section: Liquid Surface Designmentioning
confidence: 91%
“…However, once an appropriate electric potential was applied, the SAM was removed from the electrode due to reductive desorption and the microvalve became hydrophilic, and the solution flowed across the valve region. Arango et al reported the control of microfluid transportation through building electrogates in the microchannel . Different from the aforementioned integrated electrodes with hydrophobic SAMs, the electrodes they reported have semicircular trench patterns and were not modified by hydrophobic functional molecules.…”
Section: Applicationsmentioning
confidence: 99%
“…In our previous work, we showed the basics of an e-gate for stopping biological buffers, human serum, and artificial urine at a trench geometry with a semicircular shape (23). Here, we provide further analysis on the operation of e-gate arrays and their use in more complex microfluidic networks with different channel widths and Concept on controlling, monitoring, sequential delivery, and merging of multiple liquids flowing in microfluidic chips using an array of electrically actuated microfluidic gates (e-gates) and a protocol applied from a smartphone.…”
Section: Operation Principle Of Programmable Liquid Circuitsmentioning
confidence: 99%
“…The microfluidic chip and the peripheral device worked according to the protocol except for the last e-gate, which failed after holding the phosphate-buffered saline (PBS) solution for 50 min 30 s instead of 55 min (movie S4). This retention time is already long enough for many POC diagnostics applications but can be increased, if needed, using multiple e-gates connected using a cascade configuration, a wider channel for more stability, a less hydrophilic DFR, or a hydrophobic treatment applied to the Pd electrode (23).…”
Section: Programming the Flow Path Using A Smartphonementioning
confidence: 99%
“…Here, we combine capillary-driven microfluidics with battery-powered flow elements to provide a flexible method to control and tune flow rates post-fabrication. This work is based on a concept called “electrogates”, which we previously developed for stop-and-go control of flow of liquids in capillary-driven microfluidic chips 22 . Electrogates combine electrowetting 2326 with capillary pinning 27,28 to stop temporarily a liquid filling a wettable microchannel.…”
Section: Introductionmentioning
confidence: 99%